DESIGN AND ANALYSIS OF A DATA VISUALIZATION DASHBOARD FOR PT KERETA API INDONESIA (PERSERO) REGIONAL DIVISION III PALEMBANG USING THE PROTOTYPE METHOD - Nia Rahmawati; Deni Fikari (International Journal of Multidisciplinary Reseach, 2026)
The management of operational data at PT Kereta Api Indonesia (Persero) Regional Division III Palembang still relies on Microsoft Excel as the primary medium for storing, processing, and presenting data. All data analysis is carried out manually, and information is still displayed in tabular form, making it difficult for users to quickly and comprehensively understand large volumes of data, identify patterns, or observe trends. This condition results in an inefficient and time-consuming monitoring and decision-making process, as the company has not yet had an automated dashboard capable of transforming Excel data into visual information. This study aims to analyze user requirements and design a web-based data visualization dashboard using the Prototype method, which consists of five stages: Communication, Quick Plan, Modeling Quick Design, Construction of Prototype, and Deployment, Delivery and Feedback. Data were collected through observation, interviews, and discussions with the Information Systems Division. System modeling was carried out using Business Process Model and Notation (BPMN) and Unified Modeling Language (UML), including Use Case Diagrams, Activity Diagrams, and Class Diagrams, while the user interface prototype was designed using Figma. The results show that the proposed dashboard is able to accommodate the functional and non-functional requirements identified, including Excel/CSV file upload, automatic data processing, data visualization in the form of bar charts, line charts, and pie charts, as well as statistical analysis (minimum, maximum, average, and sum). The resulting dashboard prototype is expected to serve as a reference for further system development, enabling faster, clearer, and more effective data monitoring and decision-making at PT Kereta Api Indonesia (Persero) Regional Division III Palembang.